Antral follicle assessment after down-regulation may be a useful tool for predicting pregnancy loss in in vitro fertilization pregnancies - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2005)
Women with diminished ovarian reserve (OR) have a high rate of pregnancy loss. The relationship between hormonal OR tests and pregnancy loss has been studied previously, but, to our knowledge, that between the antral follicle count (AFC) and pregnancy loss has not. Therefore, we aimed to determine whether OR tests, including the AFC, can predict pregnancy loss in women achieving pregnancy by means of in vitro fertilization (IVF), and also to compare their predictive value. All women underwent a fresh cycle of intracytoplasmic sperm injection with a long protocol with mid-luteal start of the gonadotropin-releasing hormone analog, and antral follicles were counted on cycle day 3 following down-regulation. Pregnancy losses up to 12 gestational weeks (n = 28) were compared with apparently healthy deliveries (n = 34) in this retrospective analysis. Receiver operating characteristic analysis of consecutive pregnancies (n = 71) was performed to analyze the optimum cut-off value for the significantly different OR tests. Women with a pregnancy loss had a lower AFC than those with healthy deliveries. Age and hormonal OR tests were comparable between groups. The optimum cut-off value for the AFC to predict pregnancy loss was 7.5. AFC may be a useful tool for predicting pregnancy loss in IVF pregnancies.
Keywords: antral follicle; biochemical pregnancy; ovarian reserve; pregnancy loss; STIMULATING-HORMONE; OVARIAN; FSH; ESTRADIOL; COHORT; WOMEN; RISK